Evaluation of natural extracts’ antioxidant capacity for controlling fresh sausage oxidation - Bottoli, Ana Heloisa da Silveira Venzel; Peiter, Gabrielle Caroline; Bittencourt, Paulo Rodrigo Stival; Martin, Clayton Antunes; Cottica, Solange Maria (Food Science and Technology, 2023)
Lipid oxidation impacts the quality and shelf life of meat products. The use of natural antioxidants is an alternative to delay their oxidative deterioration. This study aimed to determine the antioxidant activity of natural extracts and evaluate the viability of replacing 2,3-tert-butyl-4-hydroxyanisole (BHA) in fresh sausages. Both tocopherols and grape seed extract showed similar antioxidant activity to BHA through the 2,2-diphenyl-1-picryl-hydrazyl-hydrate free radical (DPPH) and ferric reducing antioxidant power (FRAP) methods. The effectiveness of these antioxidants applied to fresh sausage was evaluated during 15 days of storage at 4.0ºC under light incidence. The results indicated a pro-oxidant effect of grape seed extract (with 6.74% acidity and 2.74 mg MDA kg sample-1 thiobarbituric acid reactive substances (TBARS)) and showed the viability of replacing BHA with tocopherols. Tocopherols had a lower peroxide value (3.07 mE O2 kg-1) than the control (11.40 mE O2 kg-1), with no difference in TBARS or acidity content compared to BHA, and the lowest total mass loss (18.22%).